The significance of employing the Quranic text in the poetry of Ibn Hani Al-Andalusi (Journal of Imam Al-Kadhim College, 2023)
The aim of this research is to demonstrate the impact of the Holy Qur’anic text with its vocabulary, meanings, and stories on the poetry of Ibn Hani Al-Andalusi, and to consider the extent to which the poet reconciled the use of these vocabulary, meanings, and stories, and how to employ them in his poetic purposes and arts, linguistically, semantically, and rhetorically, and also knowing the purpose of those The many employments, in addition to that the study tried to reveal something of the poetic experience in his life and psyche, and the religious dimension in it, and to show the impact of the outward and esoteric Ismaili beliefs in his poetry.
Keywords: Ibn Hani Al-Andalusi Semantic recruitment, The Quranic impact, The Ismaili faith, Quranic inclusion